2013
DOI: 10.3748/wjg.v19.i34.5622
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-eluting beadvsconventional transcatheter arterial chemoembolization for hepatocellular carcinoma before liver transplantation

Abstract: DEB-TACE can effectively promote tumor necrosis and improves recurrence-free survival after LT in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 37 publications
1
35
1
2
Order By: Relevance
“…DEB-TACE has been shown to be safe and effective in palliative HCC treatment in several clinical and preclinical studies (27,(36)(37)(38)(39)(40)(41), as well as in a randomized clinical trial (RCT) comparing DEB-TACE with cTACE (23,26), but the evidence to support its use as a neoadjuvant treatment before OLT is scarce (25,(42)(43)(44)(45)(46). To our knowledge, this is the first clinical study that compares OS and DFS of patients that did and did not receive DEB-TACE before OLT and one of the largest series assessing neoadjuvant DEB-TACE clinical results in the literature so far.…”
Section: Discussionmentioning
confidence: 99%
“…DEB-TACE has been shown to be safe and effective in palliative HCC treatment in several clinical and preclinical studies (27,(36)(37)(38)(39)(40)(41), as well as in a randomized clinical trial (RCT) comparing DEB-TACE with cTACE (23,26), but the evidence to support its use as a neoadjuvant treatment before OLT is scarce (25,(42)(43)(44)(45)(46). To our knowledge, this is the first clinical study that compares OS and DFS of patients that did and did not receive DEB-TACE before OLT and one of the largest series assessing neoadjuvant DEB-TACE clinical results in the literature so far.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant locoregional therapies are recommended when the expected time to LT is longer than 6 mo in order to prevent drop-out and increase long term survival, while minimizing the risk of tumour recurrence after LT [23,[66][67][68][69][70][71][72] . However many LT institutions treat most of the patients within the waiting list, since the actual time to LT may be unpredictable, and this strategy has demonstrated a favourable cost-effect balance [73] .…”
Section: Waiting List Management and Bridging Therapymentioning
confidence: 99%
“…Despite reports suggested that there was no significant difference in terms of the safety profile, tumor response, tumor recurrence and overall survival rate for DEB as compared to TACE in non-transplant patients (57,59), DEB was shown to have lower tumor recurrence rate after LT and was identified as an independent predictor of recurrence-free survival in the multivariate analysis (60). Further study should be carried out to confirm the superiority of this technique.…”
Section: Doxorubicin Eluting Bead (Deb) Transarterial Chemoembolizatimentioning
confidence: 95%